P-021 Very Delayed Monocular Blindness Following Flow Diversion Treatment of Ophthalmic Artery Aneurysm. (29th July 2016) - Higashimori, T; Sandhu, D; Kim, J; Grande, A; Ezzeddine, M; Tummala, R; Jagadeesan, B
Abstract : Introduction: Flow diversion is widely used for the effective endovascular treatment of wide-necked intracranial internal carotid artery (ICA) aneurysms. Ophthalmic artery (OA) occlusion is a known consequence related to flow diversion; however, OA occlusion in this setting usually is without clinical sequela. All reported cases of monocular vision loss after flow diversion have occurred within days to weeks of treatment. Methods: We describe a case of monocular blindness due to ophthalmic artery occlusion nearly 3 years after flow diversion treatment of tandem supraclinoid ICA aneurysms. The medical records and images were reviewed for this patient. Results: This 51 year-old woman with history of hypertension was found to have two incidental right supraclinoid ICA aneurysms following headache workup. Cerebral angiography revealed a wide neck 5 mm saccular ophthalmic aneurysm and 3 mm bi-lobed posterior communicating artery (PCoA) aneurysm. Treatment with flow diversion was performed. A 4 × 20mm Pipeline Embolization Device (PED) was deployed from the ICA terminus to the distal genu of the cavernous segment ICA without complication. She had been on dual antiplatelet therapy for 3 months followed by aspirin monotherapy. Six-month follow up angiography revealed obliteration of PCoA aneurysm, but with persistent filling of the ophthalmic aneurysm. Twenty months later, angiography again revealed persistent filling of the ophthalmic aneurysm. Both studies revealed patent right ophthalmic artery. She presented with acute onset of complete right vision loss 32 months after PED placement. MRI brain showed no acute stroke. Dilated eye exam revealed cherry red spot in macula with attenuated vessels, and retinal whitening, consistent with ophthalmic artery occlusion. Diagnostic cerebral angiography revealed occlusion of the right ophthalmic artery with patent ICA and well apposed PED without in-stent stenosis or thrombosis. The ophthalmic aneurysm was no longer filling. There were no middle meningeal collaterals to the ophthalmic artery. IA tPA was given locally near the ophthalmic artery origin with minimal improvement. She was compliant with her aspirin throughout. Conclusion: Monocular vision loss remains a risk, even months to years following flow diversion of ICA aneurysms. Long term clinical follow-up is necessary to define the incidence of this complication. Disclosures: T. Higashimori: None. D. Sandhu: None. J. Kim: None. A. Grande: None. M. Ezzeddine: None. R. Tummala: None. B. Jagadeesan: None.